Developing The Linguistic Skills of Primary School Students - Shodmonkulova Dilorom Khalikovna (Scientific Trends, 2024)
The article examines the conditions for successful speech development and the formation of speech skills and abilities in primary school students. The values of speech development are determined. The lines of formation of the culture of speech communication in primary school are identified and substantiated.
Keywords: Speech communication, conditions, speech environment, values of speech development, linguistic features of oral and written speech.